ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI MASA HIDUP POMPA BENAM LISTRIK (ELECTRICAL SUBMERSIBLE PUMP) Studi Kasus : Lapangan Kurau EMP Malacca Strait - , TRI HANDOYO; , Dr.-Ing. Awang N.I. Wardana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Work-over is one of activities related to the production wells and aims to repair the well from damage during production. Most of the work-over activities done in Kurau Field EMP Malacca Strait are an ESP installations and pull-out. Investment required for these activities is USD 0.2-0.3 million. If a pump used is no longer able to survive, it will be more often to do works-over that will give disadvantages to the company. This study will analyze the graphic relationship among some variables to the lifetime of ESP using 3 classes K-means clustering method . These variables are the types of pumps, production capacity, SG, dynamic LLC , head loss, TDH, pumps output power, and efficiency of the pumps. Besides, it discusses about mathematical analysis and correction factor analysis to get some variables. The data used in this analysis are 24 production wells data taken in Kurau Field. From the results of 3 classes K-means clustering method, it is obtained a linear relationship among the 3 class centers in each graphic between production capacity, dynamic LLC, head loss, or TDH to ESP lifetime. The linear relationship is that when the production capacity increased the lifetime of ESP will increase. While for the dynamic LLC and TDH, the greater the value, the lifetime of ESP reduces. The greater the head loss, the greater the lifetime of ESP.